Power and limitations of formal methods for software fabrication: Thirty years later - Serna M., Edgar; Serna A., Alexei (Informatica, 2017)
In 1987, Michael Jackson presented his work "Power and Limitations of Formal methods for software fabrication" at the AIT Conference, which analyzed the advantages and limitations of formal methods up to that time. His conclusion was that formal methods had undoubted capabilities and advantages, but they also had serious limitations that prevented their widespread acceptance and adoption. The aim of this paper is to present the current context of formal methods compared with what Jackson described three decades ago. A tour of the strengths and limitations of formal methods is taken through a review of literature in the timeline of the past thirty years. The conclusion is that little progress has been made on this issue in relation to the situation presented by Jackson, and formal methods still need more work from academia, industry and the community.